Acquired tick resistance: The trail is hot. (15th December 2020) - Narasimhan, Sukanya; Kurokawa, Cheyne; DeBlasio, Melody; Matias, Jaqueline; Sajid, Andaleeb; Pal, Utpal; Lynn, Geoffrey; Fikrig, Erol
Abstract: Acquired tick resistance is a phenomenon wherein the host elicits an immune response against tick salivary components upon repeated tick infestations. The immune responses, potentially directed against critical salivary components, thwart tick feeding, and the animal becomes resistant to subsequent tick infestations. The development of tick resistance is frequently observed when ticks feed on non‐natural hosts, but not on natural hosts. The molecular mechanisms that lead to the development of tick resistance are not fully understood, and both host and tick factors are invoked in this phenomenon. Advances in molecular tools to address the host and the tick are beginning to reveal new insights into this phenomenon and to uncover a deeper understanding of the fundamental biology of tick‐host interactions. This review will focus on the expanding understanding of acquired tick resistance and highlight the impact of this understanding on anti‐tick vaccine development efforts.